The effect of COVID-19 risk perception on pro-environmental behavior of Chinese consumers: Perspectives from affective event theory - Zhou, Shuai (Frontiers in Psychology, 2023)
Introduction COVID-19 has altered human cognition and changed the cultural values of society. However, there has not been much debate among scholars about whether these above changes have led to an increase in pro-environmental behavior (PEB) of Chinese consumers. Methods A comprehensive model was developed based on affective event theory. An online questionnaire was distributed, and 501 usable questionnaires were collected. In addition, two complementary approaches were employed: partial least squares structural equation modeling (PLS-SEM) and necessary condition analysis (NCA). Results The PLS-SEM results showed that COVID-19 risk perception, nostalgia, the awe of nature, and attitude were found to have a positive effect on PEB; and the moderating effect of power distance belief (PD) between nostalgia (NO), attitude (AT) and PEB was confirmed. According to the NCA results, AT and NO are necessary conditions for the PEB of consumers. Discussion This study provides deeper insight into the understanding of consumers’ pro-environmental behavior in the context of COVID-19 through the combined use of PLS-SEM and NCA.